Physical match performance of elite soccer players from the English Championship League and the English Premier League: The effects of opponent ranking and positional differences - Morgans, R.; Di Michele, R.; Ceylan, I. H.; Ryan, B.; Haslam, C.; King, M.; Zmijewski, P.; Oliveira, R. (Biology of Sport, 2025)
This study aimed to examine physical match performance and the effects of opponent ranking and positional differences in both the English Championship League (ECL) and the English Premier League (EPL) over five consecutive seasons. Fifty-four professional outfield soccer players (average age 24.6 ± 5.4 years, weight 76.6 ± 6.9 kg, height 1.79 ± 0.09 m) from an English club were involved. Physical data obtained with the 18 Hz GPS technology tracking system from 213 regular-season matches spanning the complete 2018/19 to 2022/23 seasons were examined. The results showed that, considering the level of the opponent, total distance (TD), high-intensity distance (HSR), and the number of decelerations (DEC) significantly varied in both EPL and ECL (p < 0.05, p < 0.05, p < 0.05 respectively). Additionally, opponent level influenced sprint distances (Spr) and accelerations (ACC) in the EPL (p < 0.05, p < 0.05) but not in the ECL. The highest running metrics were noted when the team played against a high-ranked opponent. Concerning positional roles, more physical metrics were influenced by opponent level in the ECL (centre-backs (TD, ACC), full-backs (TD, DEC), centre midfielders (TD, HSR, Spr, DEC), attacking midfielders (TD, Spr, DEC), centre forwards (TD)) than in the EPL (centre midfielders (TD, HSR, DEC), attacking midfielders (TD, DEC), centre forwards (TD)). These findings contribute to a more comprehensive understanding of how players from different positions perform in elite soccer match-play against varying opposition rankings. Coaches may then tailor tactical approaches, positional, and individualized training regimens to address the specific physical demands associated with matches against different-ranked opponents.